Biomechanical Pathways in Volleyball Spike Performance A Path Analysis of Anthropometric and Technical Factors - Muhammad Syaleh; M. Ghozali Aufathul Akbar; Fadhil Ammar Rizqillah Lubis; Bastian Pratama Lumban Gaol; Boy Agustinus Sirait; Boisandi Buulolo; Yunita Mandasari; Dian Buono; Aulia Hidayati Ramadhana; Yupiter Prakasa Laia; Eka Selvia Tampubolon (Joska: Jurnal Isori Kampar, 2024)
Objectives: To examine the biomechanical factors influencing volleyball spike performance through path analysis, investigating direct and indirect relationships between anthropometric measurements, physical capabilities, and technical execution parameters. Methods: Sixty elite volleyball players (30 male, 30 female) underwent comprehensive biomechanical testing, including anthropometric measurements, strength assessments, coordination tests, and performance measures. Path analysis was conducted using AMOS 26.0 software with bootstrapping (5000 samples) to evaluate relationships between variables. Multiple goodness-of-fit indices were used to assess model validity. Results: Arm length demonstrated the strongest direct effect on spike velocity (β = 0.45, p < 0.001), with a total effect of β = 0.57 when including indirect pathways. Core strength significantly influenced spike performance through coordination (β = 0.35, p < 0.001). Shoulder rotational strength directly affected ball speed (β = 0.39, p < 0.001), while reaction time significantly influenced approach timing (β = -0.32, p < 0.01). The model showed good fit with RMSEA = 0.048 (90% CI: 0.039-0.057), CFI = 0.962, and TLI = 0.955. Conclusion: The study revealed complex interrelationships between anthropometric characteristics, physical capabilities, and technical execution in volleyball spike performance. Both direct physical attributes and their indirect effects through technical parameters contribute to successful spike execution. These findings provide evidence-based recommendations for training program design and talent development in volleyball.